L’expérience touristique dans les guides : une subjectivité à lire, écrire et raconter - Hécate Vergopoulos; Emilie Flon (Belgeo)
This paper deals with tourist experience. Through a communicational approach of a textual device (i.e. travel guides), it analyses three different ways of constructing a possible experience of tourist places. It shows that experience can be seized as an observed fact, a lived-through experiment or a experiment to be lived through. To understand this polymorphism, it studies the symbolic representations of various actors engaged in tourist mediation: the author, the reader who travels or co-mediates and the narrator. It shows that these figures are ambiguous in the sense that they are defined in the framework of both a writing/reading situation (the one of the book) and a visit situation (the one that lead to the printing of the guide and/or the one the guide invites to achieve). It enlightens the fact that it is through these figures that travel guides construct their experiences of territories: these experiences have to do with subjectivity, i.e. a social and touristic relation to territories.